Preparing a fish embryo (Prochilodus lineatus) for staging, chorion removal and PGC traceability - Coelho, Geovanna C. Z. [UNESP]; Yo, Isaac S.; Mira-Lopez, Tatiana M.; Monzani, Paulo S.; Arashiro, Dilberto R. [UNESP]; Fujimoto, Takafumi; Senhorini, Jose A. [UNESP]; Yasui, George S. [UNESP] (Univ Basque Country Upv-ehu Press, 2019)
The transplantation of primordial germ cells (PGCs) is a valuable tool for gene-banking and reconstitution by means of a germline chimera. For this technology, studies regarding developmental stages and traceability of PGCs are necessary. The objective of this study was to develop a micromanipulation procedure for the future establishment of cryobanks of PGCs in migratory characins. Incubation temperatures were evaluated at 22 degrees C, 26 degrees C, and 30 degrees C in order to synchronize developmental stages. The highest hatching rates and the lowest abnormality rate arose at 26 degrees C, which was considered to be the best incubation temperature. Enzymatic removal of the chorion was determined to be best using 0.05% pronase, in which the embryos presented better survival rates. In order to visualize PGCs in vivo, artificial GFP-nos1 3'UTR mRNA was injected and the migration route was observed in vivo as PGCs were visualized firstly at the segmentation stage (6 to 13 somites). The number of GFP positive cells ranged from 8 to 20 per embryo (mean of 13.8; n = 5). After hatching, GFP-positive cells increased to 14 to 27 embryos (mean of 19.8; n = 5). Visualization of the GFP-positive cells was possible at 10 days post hatching, and at this stage, the cells were positioned in the yolk extension region. This is the first report on PGC visualization in vivo in Neotropical fish; the obtained data provide information on the identification and migration of PGCs. The information presented in this work brings new insights in gene banking in Neotropical species and subsequent reconstitution through a germinal germline chimera.
Keywords: biotechnology; genebank; germline chimera; primordial germ cell; teleost